Issues in Interest Rate Management and Liberalization. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This paper discusses the transition strategy from administratively set interest rates to market rates. Despite worldwide trends toward financial liberalization, few monetary authorities are prepared to accept as reasonable any interest rate level that is market-determined. The paper suggests some helpful indicators to assess the adequacy of interest rates. It discusses factors which contribute to a smooth liberalization process. The main conclusion is that interest rate liberalization is not synonymous with laissez-faire policies. It requires, however, the replacement of the administratively set interest rates by indirect monetary management techniques which operate through the market.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet